Sistem Pengembangan dan Pemberdayaan Budaya Sekolah di Mts Aisyiyah Sumatera Utara - Elin Suryani (Jurnal Ilmiah Wahana Pendidikan, 2023)
School Culture at MTs Aisyiyah North Sumatra is the result of an agreement between the school principal, teaching staff, education staff, and the PWA Elementary School. School culture is determined according to the vision, mission, goals and objectives to be achieved. In designing the school culture, the principal as the leader studied a SWOT analysis from the Mts Aisyiyah North Sumatra school. Includes: strengths, weaknesses, opportunities, threats in order to determine the factors that influence the success of the Mts Aisyiyah North Sumatra school. The system for developing and empowering culture carried out by school principals and teachers is by making clear rules that are notified in class or during ceremonies or at the commemoration of religious holidays. The way to institutionalize school culture among students is in the form of institutional school culture. (1) Through religious education. (2) Through posters, ritual images or calligraphy. (3) Through religious activities such as congregational prayers, reciting the Koran and Islamic boarding schools, (4) Through providing insight into the function of humans as social beings who are created as weak creatures and need other people. (5) Through habituation of discipline from an early age. The school culture that has been implemented has a major influence on success in achieving the school's vision and mission, this is assessed from the formation of students' attitudes that are noble, capable, confident, and independent. The culture that is applied at Mts Aisyiyah North Sumatra is one of the solutions that schools do in overcoming weaknesses and deficiencies that occur in teachers, students and weaknesses in the work system at this school.